Sustainable Social Supply Chain Practices and Operational Performance in The Manufacturing Industry in Sleman - Tri Wahyuningsih; Yuli Liestyana; Yekti Utami; Hadi Oetomo; Tugiyo Tugiyo (Journal of International Conference Proceedings, 2025)
This research aims to explore how Sleman Regency's manufacturing sector operates in relation to sustainable social supply chain practices (SSSCPs).  The primary data used in this investigation were obtained from questionnaires.  After the data was gathered, the connection between the variables was examined using linear regression analysis. The analysis's findings show that operational performance (OP) is positively impacted by sustainable social supply chain practices (SSSCPs). With a small sample size of 37, the generalizability of this study is limited to medium- and large-scale manufacturing industries in Sleman Regency that have been in operation for at least ten years.  However, by examining these connections in a developing nation, this study offers a fresh viewpoint. By investigating the impact of sustainable social supply chain practices (SSSCPs) on operational performance (OP) in the industrial sector of Sleman Regency, this study adds to the body of literature.  From a practical standpoint, this study helps manufacturing firms understand The value of applying measures that promote social responsibility within sustainability to enhance overall competitiveness and operational performance.